2021
DOI: 10.1007/s00277-021-04687-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors associated with induction-related death in acute myeloid leukemia in a resource-constrained setting

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Kirkizlar et al found that in leukaemia patients colonised with VRE, a low neutrophil count and coinfection were associated with increased mortality [ 96 ]. Mendes et al included VRE in a bivariable screening but discarded the factor as it did not meet the criterion of p < 0.1 [ 55 ]. Ornstein et al found that leukaemia patients with a VRE bacteraemia at the induction of chemotherapy had poorer survival than patients with other bloodstream infections [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kirkizlar et al found that in leukaemia patients colonised with VRE, a low neutrophil count and coinfection were associated with increased mortality [ 96 ]. Mendes et al included VRE in a bivariable screening but discarded the factor as it did not meet the criterion of p < 0.1 [ 55 ]. Ornstein et al found that leukaemia patients with a VRE bacteraemia at the induction of chemotherapy had poorer survival than patients with other bloodstream infections [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kirkizlar et al found that in leukaemia patients colonised with VRE, a low neutrophil count and coinfection were associated with increased mortality (92). Mendes et al included VRE in a bivariable screening, but discarded the factor as it did not meet the criterion of p<0.1 (51). Ornstein et al found that leukaemia patients with a VRE bacteraemia at the induction of chemotherapy had poorer survival than patients with other bloodstream infections (93).…”
Section: Resultsmentioning
confidence: 99%
“…In total, there were 23/144 (16%) studies of patients with solid cancers , 65/144 (45%) studies of patients with haematological cancers (41-105), and 56/144 (39%) studies with patients of both or unspecified cancer types (106-161). Most studies selected (39/144, 27%) reported and modelled several bacteria and/or fungi that were tested for resistances towards several antimicrobials (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(106)(107)(108)(109)(110)(111)(112)(113)(114)(115). Eight of 144 (6%) reporting and modelling several microorganisms focused only on Gram-negative bacteria (54)(55)(56)(57)(58)(116)(117)(118)) and 1/144 (1%) focused only on fungi (59).…”
Section: Studies Selectedmentioning
confidence: 99%
See 1 more Smart Citation
“…To predict patients at high risk for D30 death, various factors are suggested. Mendes et al suggested that age, Gram-negative bacterial infection, monocytic AML, increased C-reactive protein (CRP), and adverse genetic risks were associated with an increased risk of 60-day mortality [ 18 ]. Sasaki et al suggested the following prognostic factors for D30 death after intensive chemotherapy (CTx): age, ECOG performance status, infection at diagnosis (pneumonia), cytogenetics (complex karyotype), total bilirubin, and creatinine and uric acid [ 16 ].…”
Section: Introductionmentioning
confidence: 99%